Neoplasias primárias do sistema nervoso central em animais domésticos (2000-2021) - Nunes, Marcus Vinícius Lima (2021)
Primary neoplasms of the nervous system are rare in domestic animals, being more frequently reported in dogs older than five years. They are classified according to the cellular origin, form of growth and the degree of cell differentiation. However, the cellular origin and the histogenesis of some neoplasms are still poorly understood. The gold standard for diagnosis and characterization of malignancy, with few exceptions, remains the histopathological examination, however, in poorly differentiated neoplasms, it is necessary to use the immunohistochemistry technique for diagnosis and prognosis. Thus, the objective of this study is to classify by histopathology and immunohistochemistry the neoplasms of the central nervous system referred for diagnosis at the Veterinary Pathology Sector of UFLA in a period of 21 years (2000-2021), correlating with epidemiological aspects. as primary antibodies, anti-BIII tubulin, -NeuN, -neuron specific enolase, -Olig2, -Glial fibrilary acid protein (GFAP), -neurofilament, -S-100, -chromogranin, -synaptophysin, -pancitokeratin, -vimentin and –proliferating cell nuclear antigen (PCNA) were used. Thirteen CNS neoplasms were found. Based on microscopic and immunohistochemical characteristics, these were classified as transitional meningioma, grade I (2/13), transitional meningioma, grade II (1/13), psammomatous meningioma, grade II (1/13), papillary meningioma, grade III (1/13), oligodendroglioma, grade III (3/13), astrocytoma, grade IV (1/13), occurring in canines (9/13), well differentiated teratoma in sheep (1/13) and ependymoma in bovine (1/13). In two neoplasms (2/13) it was not possible to reach the definitive diagnosis, one in the bovine spinal cord and the other in the brain of an equine. The results showed a greater occurrence of CNS neoplasms in canines, with meningioma being the most frequently found. Thus this study contributed to a better understanding of morphological and immunohistochemical aspects of CNS tumors in domestic animals.